2013
DOI: 10.1111/pace.12210
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Prognosis for Clot Formation on Cardiac Device Leads

Abstract: Patients with AF are at higher risk for clot formation on device leads. After clot detection, treatment with anticoagulants usually results in resolution of the clot without embolic phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…Our data supports the study by Rahbar et al,[21] where they showed that the initiation of intensified anticoagulation therapy resulted in reduction or shrinkage of thrombus in 9 of their patients whom they had follow up data on. The one major limitation of their study is that they only used TTE as the imaging modality.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data supports the study by Rahbar et al,[21] where they showed that the initiation of intensified anticoagulation therapy resulted in reduction or shrinkage of thrombus in 9 of their patients whom they had follow up data on. The one major limitation of their study is that they only used TTE as the imaging modality.…”
Section: Discussionsupporting
confidence: 92%
“…Our data is similar to Rabher et al[21] who reported lead thrombus in 1.4% of their population who underwent a TTE. Our incidence is smaller when compared to Supple et al,[18] who reported thrombus at 30%.…”
Section: Discussionsupporting
confidence: 92%
“…In two patients, we observed complete resolution of the echogenic mass. This is consistent with a recently reported case series by Rahbar et al in which eight out of nine patients had some response to intensification of warfarin therapy and seven out of nine had complete resolution of the echogenic masses [16]. In their case series, none of the patients who had resolution of the echogenic mass had a therapeutic INR prior to intensification of warfarin therapy.…”
Section: Discussionsupporting
confidence: 91%
“…There are a few cases reported in literature in which a clot was formed on the pacemaker lead 9. Our presenting patient had a pacemaker lead in the RA, but the mass origin revealed in surgery was away from the leads.…”
Section: Discussionmentioning
confidence: 75%